Identifikasi dan Analisis Populasi Gulma Pada Budidaya Tanaman Padi Organik dan Non Organik - Elisabet Sartiana Saitun; Farida Hanum; I Dewa Nyoman Raka (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
The purpose of this study is (1) for any kisnd of weed that grows on the fields of organic and non-organic rice crops (2) To determine whether the dominant weed grows on the organic and non-organic felds in the countryside using a quadratic method aimed at surveying locations, data gathering is done directly in the field by means of a vegetation analysis method and the square method that is a spot-of plot observations in the field. This research shows the type and species of weed found in Negari,kecamatan banjarangkan ,kabupaten klngkung.this research was conducted using the quadratic method directed by a site survey,data collection was carried out directly in the field using the vegetation analysis method, namely by observing the sampel plot in the field.the results of the study showed the types and species of weeds found in organic and non organic rice defenses in the village of negari banjarangkan,banjarangkan sub district,klungkung district,consisted of 5 species, namel: Monochoria vaginalis, pistia stratiotes Cyperus rotundus L, Echinochloa crussgalli, Marsilea clover in non oganic rice consists of 6 species Ludwigia adscendens, Cyperus rotundus L, Echinochloacrussgalli, Monochoriavaginalis, Limnocharis flava L, Marsilea clover. The highest index of importance for organic rice is Monochoriavaginalis 89,16% in non oganic rice , Echinochloacrussgalli 60,80% and the lowest importance value index for organic rice Marsilea clover 30,28% in non organic rice : Ludwigia adscendens 32,51%